Modulatory effect of two regimens of magnesium sulfate on the systemic inflammatory response in pregnant women with imminent eclampsia - Peraçoli, José Carlos (2022)
Objective: This study compared the modulatory effect of two intravenous magnesium sulfate (MgSO4) regimens on the systemic inflammatory response in pregnant women diagnosed with imminent eclampsia. Study design: In a single-blind cross-sectional study, 33 women were allocated according to the Zuspan (n = 16) and Sibai (n = 17) MgSO4 regimens, and treated for 24 h. Blood samples were collected pre-administration of the loading dose, at 24 h of the maintenance dose of MgSO4, and at 48 h, when patients were without treatment. Plasma was used to determine interleukin (IL)-1 beta (IL-1β), IL-6, IL-10, tumor necrosis factor-alpha (TNF-α), heat shock protein (Hsp70), and heme oxygenase-1 (HO-1) by ELISA. Results: The treatment with the Zuspan’s regimen didn’t change plasma concentrations of TNF-α, IL-10, and Hsp70 in the three-time points studied. However, it decreased IL-1β at 24 h and 48 h and IL-6 at 48 h, and increased HO-1 concentration at 48 h. On the other hand, compared to the pre-treatment period, Sibai’s regimen induced a significant decrease in TNF-α, IL-1β, IL-6, and Hsp70, while increased HO-1 levels both at 24 h and 48 h and, IL-10 concentration at 48 h. Conclusions: Sibai’s regimen determined an early and efficient immunoregulatory effect on systemic inflammatory response in preeclampsia, suggesting that the maintenance dose of two grams of MgSO4 was better than one gram in the treatment of imminent eclampsia.